2015
DOI: 10.1080/09540121.2014.999744
|View full text |Cite
|
Sign up to set email alerts
|

Integrating family planning and HIV services in western Kenya: the impact on HIV-infected patients’ knowledge of family planning and male attitudes toward family planning

Abstract: Little information exists on the impact of integrating family planning (FP) services into HIV care and treatment on patients’ familiarity with and attitudes toward FP. We conducted a cluster-randomized trial in 18 public HIV clinics with twelve randomized to integrated FP and HIV services and six to the standard referral-based system where patients are referred to an FP clinic. Serial cross-sectional surveys were done before (n=488 women, 486 men) and after (n=479 women, 481 men) the intervention to compare ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…), the average FP awareness score increased significantly between the pre‐ and post‐intervention periods among women at both the integrated and usual care sites, but awareness at endline was no higher among women attending the clinics with integrated FP compared to regular sites (Onono et al. ). This nondifferential improvement across sites might be attributable to the training providers received at comparison sites.…”
Section: Outcome Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…), the average FP awareness score increased significantly between the pre‐ and post‐intervention periods among women at both the integrated and usual care sites, but awareness at endline was no higher among women attending the clinics with integrated FP compared to regular sites (Onono et al. ). This nondifferential improvement across sites might be attributable to the training providers received at comparison sites.…”
Section: Outcome Resultsmentioning
confidence: 97%
“…The evaluation of the randomized trial in Kenya found a favorable improvement in the attitude of men attending HIV care programs at the integrated sites, with a 12 percent decline in men's agreement with the statement that FP is “women's business” that was statistically significantly different from the men at the usual care sites (Onono et al. ). HIV care and treatment may be an opportune environment to engage men in FP.…”
Section: Outcome Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More research is required to understand how improved gender equity might be leveraged to increase access to HIV testing and treatment, contraceptive use, and other reproductive health outcomes (Hawkes and Buse ; Onono et al. ; Ghanotakis et al. ; Newmann et al.…”
Section: Future Directionsmentioning
confidence: 99%
“…Because many individuals may not be able to disclose HIV status and/or bring their partner to clinic, sexual and reproductive health and HIV prevention programs need to cater to individual-level as well as couples-based consultation [73]. Male-friendly environments may promote male health-seeking behaviors, including engaging in pre-conception care [74]. …”
Section: How Can Programs Identify Individuals Who May Benefit From Pmentioning
confidence: 99%